2019
DOI: 10.3390/ijms20164016
|View full text |Cite
|
Sign up to set email alerts
|

Potential for Tight Junction Protein–Directed Drug Development Using Claudin Binders and Angubindin-1

Abstract: The tight junction (TJ) is an intercellular sealing component found in epithelial and endothelial tissues that regulates the passage of solutes across the paracellular space. Research examining the biology of TJs has revealed that they are complex biochemical structures constructed from a range of proteins including claudins, occludin, tricellulin, angulins and junctional adhesion molecules. The transient disruption of the barrier function of TJs to open the paracellular space is one means of enhancing mucosal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 125 publications
0
18
0
Order By: Relevance
“…Several other studies have used CLDN-4 as a target for tumor therapy and showed the accumulation of anti-CLDN-4 mAbs specifically in the tumors and reduced the growth of human colorectal and gastric tumors in mice [150]. One study detected CLDN-4 upregulation non-invasively in mice pancreatic ductal adenocarcinoma xenografts by using MRI and 18 FDG-PET [151] (for detailed reviews see [152]). In the future, a similar approach can be applied to CLDN-1 by preparation of CLDN-1 targeting molecule and can be tested for cytotoxicity to normal cells.…”
Section: Claudin-1 As a Drug Targetmentioning
confidence: 99%
“…Several other studies have used CLDN-4 as a target for tumor therapy and showed the accumulation of anti-CLDN-4 mAbs specifically in the tumors and reduced the growth of human colorectal and gastric tumors in mice [150]. One study detected CLDN-4 upregulation non-invasively in mice pancreatic ductal adenocarcinoma xenografts by using MRI and 18 FDG-PET [151] (for detailed reviews see [152]). In the future, a similar approach can be applied to CLDN-1 by preparation of CLDN-1 targeting molecule and can be tested for cytotoxicity to normal cells.…”
Section: Claudin-1 As a Drug Targetmentioning
confidence: 99%
“…For example, Klebsiella oxytoca -induced antibiotic-associated hemorrhagic colitis and diarrhea occur mainly to the secreted cytotoxins tilivalline and tilimycin, which induce apoptosis, while in addition, independently of these, Klebsiella oxytoca also affects claudin-5 and -8 and thus paracellular barrier integrity [ 1 ]. Toxins like Clostridium perfringens enterotoxins (CPEs) are also known to directly interact with claudins and have come into focus for use as tools targeting claudins specifically [ 2 , 3 ].…”
Section: Tight Junction Barriers and Structuresmentioning
confidence: 99%
“…Such toxins can bind to specific TJ proteins; it is known that CPE can bind to members of the claudin family and that the Clostridium perfringens iota-toxin can bind to other TJ proteins such as the angulins. Peptide fragments that still possess binding capacities can be either used based on their direct binding to their original targets or can be mutated to gain binding specificity for other TJ proteins [ 3 ]. In detail, the mutation of the claudin-binding domain of CPE (cCPE) leads to its binding to the usually-not-targeted claudin-1, which is involved, for example, as a co-receptor for hepatitis C virus (HCV) infections or is a main component of the epidermal barrier limiting drug delivery.…”
Section: Tight Junction Barriers and Structuresmentioning
confidence: 99%
“…Obvious dysregulation of claudin expression has been found in a number of cancer tissues. Owing to the specific expression profile and differences between normal and tumor cells, claudins are attractive targets that can theoretically enable selective drug delivery with minimal adverse events ( 3 ). To effectively target claudins for clinical applications, it is essential to understand their roles and fully elucidate the complicated mechanisms by which the expression of claudins is dysregulated in cancer.…”
Section: Introductionmentioning
confidence: 99%